PERANCANGAN BONEKA KAYU KARAKTER PAKAIAN ADAT TRADISIONAL JAWA BARAT - Adenin, Sarah Diliani; Desanto, Didik; Rohaeni, Ai Juju (ATRAT: Jurnal Seni Rupa, 2021)
The idea of making Wooden Dolls Characters of Traditional West Java Traditional Clothing originated from the desire to develop souvenirs typical of West Java which is currently lacking in terms of innovation and in terms of product form development. The process of the creation method will go through several stages which include: 1) interview, 2) design making, 3) sketching, 4) realization. In the data collection method used in the design of this final project, a literature study was carried out by collecting data about existing similar products from reference books, journals, internet. The main medium of this work is the manufacture of wooden dolls with characters from traditional West Javanese clothes designed for souvenirs typical of West Java. The manufacturing process is carried out through the exploration of patterns, shapes, techniques, and materials. This final work still requires a thorough trial and exploration of various factors that must be considered in the design of this wooden doll.Â Keywords: Wooden Doll, West Java Traditional Traditional Clothes------------------------------------------------------------------------------------------Gagasan membuat Boneka Kayu Karakter Pakaian Adat Tradisional Jawa Barat berawal dari keinginan mengembangkan produk cendramata khas Jawa Barat yang saat ini kurang dalam segi inovasi dan dalam segi pengembangan bentuk produknya. Proses metode pengkaryaan akan melalui beberapa tahap yang meliputi: 1) wawancara, 2) membuat desain, 3) membuat sketsa, 4) realisasi. Dalam metode penelusuran data yang digunakan dalam perancangan tugas akhir ini adalah Studi literatur dilakukan dengan pengambilan data mengenai produk sejenis yang sudah ada sebelumnya baik yang bersumber dari buku acuan, jurnal, internet. Media utama karya ini berupa pembuatan boneka kayu karakter pakaian adat tradisional Jawa Barat yang dirancang untuk produk cendramata khas Jawa Barat. Proses pembuatan dikerjakan melalui eskplorasi pola, bentuk, teknik, dan bahan. Karya akhir ini masih memerlukan uji coba dan eksplorasi secara menyeluruh terkait berbagai faktor yang harus diperhatikan dalam perancangan boneka kayu ini.Â Kata Kunci: Boneka Kayu, Pakaian Adat Tradisional Jawa Barat